2020
DOI: 10.1038/s41598-020-69257-8
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical microstructure strengthening in a single crystal high entropy superalloy

Abstract: By contrast, the APT reconstructions in Fig. 2b shows an interesting hierarchical microstructure, in addition to the FCC matrix and the L1 2 phases, there were nano-particles dispersion within the L1 2 phase. These nanoparticles were only present in the HT-2 state, not in the previous HT-1 state. Compositions of each phase in HT-2 state are summarized in Table 1. The calculated partitioning coefficients of Al,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Chen, Chang [56] studied the hierarchical microstructural strengthening of HESAs and the composition of strengthening elements can consist of Cu, Fe, Ti, Zr, Co, V, Al, Nb, Cr and Mn. While the overall structure can comprise Mn, Ni, Fe, Ti, Co, Cr and V while for the grain boundary strengthening; C, B and Hf are added but must not be over 15% of the superalloy's total compositional weight.…”
Section: High Entropy Superalloys (Hesas)mentioning
confidence: 99%
“…Chen, Chang [56] studied the hierarchical microstructural strengthening of HESAs and the composition of strengthening elements can consist of Cu, Fe, Ti, Zr, Co, V, Al, Nb, Cr and Mn. While the overall structure can comprise Mn, Ni, Fe, Ti, Co, Cr and V while for the grain boundary strengthening; C, B and Hf are added but must not be over 15% of the superalloy's total compositional weight.…”
Section: High Entropy Superalloys (Hesas)mentioning
confidence: 99%
“…The high-entropy solid solutions are typically FCC alloys, BCC alloys, and also amorphous-structured alloys (high-entropy bulk metallic glass), but HCP-structured alloys were also reported [3]. Actually, there has been a great increase in the number of works that report on these novel microstructures with excellent properties [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This research focuses on recently developed HESA [8]. HESA has an approximately 70 % volume fraction of the γ precipitates, which could make it a candidate for such materials as turbine blades [9,10]. The previous research on microstructural characterizations of HESA by heat treatment conditions revealed that the primary γ precipitates grow rapidly and change in their shape from the original microstructure over 870 • C [11].…”
Section: Introductionmentioning
confidence: 99%